Resident perceptions of the impact of duty hour restrictions on resident-attending interactions: an exploratory study - Kristen A. Gerjevic; Marcy E. Rosenbaum; Manish Suneja (BMC Medical Education, 2017)
Abstract Background The institution of duty hour reforms by the Accreditation Council for Graduate Medical Education in 2003 has created a learning environment where residents are consistently looking for input from attending physicians with regards to balancing duty hour regulations and providing quality patient care. There is a paucity of literature regarding resident perceptions of attending physician actions or attitudes towards work hour restrictions. The purpose of this study was to identify attending physician behaviors that residents perceived as supportive or unsupportive of their compliance with duty hour regulations. Methods Focus group interviews were conducted with residents exploring their perceptions of how duty hour regulations impact their interactions with attending physicians. Qualitative analysis identified key themes in residents’ experiences interacting with faculty in regard to duty hour regulations. Forty residents from five departments in two hospital systems participated. Results Discussion of these interactions highlighted that attending physicians demonstrate behaviors that explicitly or implicitly either lend their support and understanding of residents’ need to comply with these regulations or imply a lack of support and understanding. Three major themes that contributed to the ease or difficulty in addressing duty hour regulations included attending physicians’ explicit communication of expectations, implicit non-verbal and verbal cues and the program’s organizational culture. Conclusions Resident physicians’ perception of attending physicians’ explicit and implicit communication and residency programs organization culture has an impact on residents’ experience with duty hour restrictions. Residency faculty and programs could benefit from explicitly addressing and supporting the challenges that residents perceive in complying with duty hour restrictions.